Revisiting Langsdorffia Hypogaea (Balanophoraceae) from the perspective of phytosite and biodiversity conservation (Revista Espinhaço, 2026)
This study expands the records of the species Langsdorffia hypogaea Mart. (Balanophoraceae) in the Triângulo Mineiro/Alto Paranaíba region, specifically in the municipality of Monte Carmelo, Minas Gerais, adding 48 new occurrence points and discoveries about its autocorrelation pattern over a two-year monitoring period. For the first time, we report a photographic record of a floral visitor, such as an ant, interacting with L. hypogaea in this ecoregion. Based on field observations of the phenological period between 2024 and 2025 and an examination of public records, it was possible to outline a timeline of the species' flowering and senescence. Additionally, we propose the development of the idea and concept of a "phytosite" based on the ecological and spatial recurrence of the species, characterizing a specific landscape unit within the boundaries of Parque da Matinha, with distinct edaphic, topographic, and vegetation cover attributes.
Keywords: Rosa-de-caboclo; Holoparasite; Pollination; Landscape Management